Immune Microenvironments of Anal Cancer Precursors Differ by HIV-Serostatus and are Associated with Ablation Outcomes. (4th October 2017) - Gaisa, Michael; Liu, Yuxin; Arens, Yotam; Sigel, Keith
Abstract: Background: HPV-associated anal cancer precursors (high-grade squamous intraepithelial lesions, HSIL) follow a more virulent course in HIV+ patients than in their HIV− counterparts. This study aims to characterize the subpopulations of mucosa-infiltrating T lymphocytes in HSIL microenvironments, correlating them with HIV−serostatus and electrocautery ablation (EA) outcomes. Methods: Using immunohistochemistry, we quantified mucosa-infiltrating CD4+ and CD8+ T lymphocytes in 115 HSIL (from 70 HIV+ and 45 HIV− patients) and 20 benign anal mucosa samples (from 10 HIV+ and 10 HIV− patients). Clinicopathological parameters were collected and compared by HIV status. Results: Patients' age, cytology diagnoses, and HPV types were comparable between HIV+ and HIV− groups. In benign controls, T lymphocytes were sparse in both HIV+ and HIV− anal mucosa. The number of total mucosa-infiltrating T lymphocytes and the CD8+ subset were significantly higher in anal HSIL from HIV+ subjects than in those from HIV− subjects (mean 71 vs. 47; 46.5 vs. 22/HPF, P < 0.001) whereas the CD4+ subset was similar between groups (24.5 vs. 25/HPF, P = 0.4). Among patients who underwent EA, subsequent anoscopy and biopsy detected persistent anal HSIL in 21/51 (41%) HIV+ and 5/27 (19%) HIV− patients ( P = 0.04, mean 12-month follow-up, range 3-36). Unadjusted analysis showed a trend towards EA failures associated with HIV seropositivity (OR 2.0; 95% CI 0.80–4.9) and increased number of mucosa-infiltrating CD8+ T cells (OR 2.3; 95% CI 0.9-5.3). Conclusion: Anal HSIL immune microenvironments differ significantly by HIV serostatus. HSIL in HIV+ subjects with increased mucosa-infiltrating CD8+ T cells tended to persist after EA. Therapies that target mucosal immunity may improve treatment outcomes of those lesions. Disclosures: All authors: No reported disclosures.